Studi integrasi tata ruang pemukiman transmigrasi : dengan studi kasus 5 lokasi, Sabulussalam, Ipuh Sebelat, Kurau, Malonas, Nabire : laporan akhir (Planars, 1984)
Integrated space use in transmigration settlements in Indonesia; case study of representative sites in five provinces.